Historical memory and the identity of places - Farinelli, Patrizia (Ars et humanitas, 2019)
In this article we will examine the form taken by memories of the war in Yugoslavia during the 1990s in the novel Zone (2008) by Mathias Énard and in the collection of documentary prose La guerra in casa (1998) by Luca Rastello. Our aim is to show that in both works, albeit in different ways, the memory of violent historical events opens up a new approach to the identity of places according to which the identity of this place is not imaginable except in relational terms. Whilst in eyewitness accounts from the collection La guerra in casa, places and geographical areas are redefined only in the categories of ''within'' and ''outside'' of ''over there'' and ''over here'' (places where people had direct experience of war and violence and those where people remained at that time outside it), in É n a r d 's novel they have a more fluid identity. The ''here'' and the ''there'' tend to be more entwined because of their shared fate; at the same time also history is represented as a network: individual and collective experiences, the past and the present, the historical and the mythical dimensionsoften intersect.
Keywords: documentary prose; dokumentarna proza; Énard, Mathias; fiction; fikcija; francoski roman; French novel; geografski prostori; geographical spaces; history; Italian literature; italijanska književnost; Jugoslavija; memory; prostor; Rastello, Luca; space; spomin; vojna; war; Yugoslavia; zgodovina